Mickey 17 [videorecording (DVD)] - Pong, Chun-ho, 1969-; Pattinson, Robert, 1986-; Ackie, Naomi; Yeun, Steven; Ferran, Patsy; Britton, Cameron, 1986-; Henshall, Daniel, 1983-; Park, Stephen, 1951-; Vartolomei, Anamaria, 1999-; Collette, Toni; Ruffalo, Mark; Chŏng, Chae-il, 1982-; et al. (Warner Bros. Entertainment Inc., 2025)
Unlikely hero Mickey Barnes finds himself in the extraordinary circumstances of working for an employer who demands the ultimate commitment to his job: to die for a living.